Scaffolding speaking fluency using the videoblog portfolio - Shuib, Muhammad Asyraf; Ismail, Lilliati; Abdul Manaf, Umi Kalthom (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
With the upsurge of technological advancement, the internet and social media, many studies on instructional practices in English Second Language (ESL) classrooms with the use of technology have been carried out to match the 21st century learning climate. Practitioners, curriculum designers and scholars continue to explore the potentials of using various media tools that can support teaching and learning. Today, frequent engagement with social media and the internet has allowed learners to sharpen their English language communication skills. This study explored the potentials of using video blogging portfolio to improve speaking fluency among ESL learners at a higher learning institution in Malaysia. The researchers employed an exploratory single case study to mitigate the existing gap that is linked to the limited opportunity and exposure Malaysian ESL learners have to communicate using the second language, L2. In the effort of encouraging communication using the language, the researchers employed the use of the social media platform, as the vlog-portfolio to systematically compile learners’ communicative activities. An instructional module was designed by the researchers and integrated into an existing curriculum as a project based learning. Field observations and post interviews were used to identify the scaffolding techniques employed by the learners. Fluency and pause rates were also measured to determine the outcome of the project. The findings revealed that learners showed developmental patterns in their speech fluency rates. A focus group interview revealed that learners were able to practice English extensively with the vlog-portfolio project. Besides producing speech, they also actively participated in assessing their spoken language performance through peer-reviewing sessions using a qualitative case study document which encouraged self-assessment, peer-assessment and reflective practices among learners. The researchers concluded that the vlog-portfolio is beneficial as a learning tool as it complements instructional needs, encourages feedback, helps learners improve on fluency, and allows learners to practice speaking using a social media platform.